Online Gambling Handling Strategies through a Civil Forfeiture Legal Approach - Ujung, Yade Setiawan (Journal of Governance, 2025)
The rise of online gambling poses significant legal and social challenges, requiring effective countermeasures. This study examines the strategy for addressing online gambling through a civil forfeiture legal approach. Utilizing a normative juridical method, the research analyzes regulations, case studies, and legal frameworks related to asset confiscation from online gambling activities. The findings indicate that civil forfeiture provides a preventive and repressive mechanism to disrupt illegal financial flows and deter perpetrators. However, implementation faces obstacles such as legal inconsistencies and enforcement limitations. The study concludes that strengthening legal instruments, interagency coordination, and public awareness are essential to optimizing civil forfeiture in combating online gambling